Innovative Marketing Practices Suiting the Current Social Behaviour of Indian Customers - Kameswara Sastry, B. V. H.; Chandrashekar, D. V. (Indian Journal of Marketing, 2009)
The globe is spinning at a very rapid pace and the world of marketing is in the revolution mode. The customers of modern India are far different from the ’Me Too’ category of customers, they are the rebellions. They want to look different, consume different and behave differently. The customers, their needs, their buying behaviour and expectations has transformed radically over the period of time. These changes have made the marketers to think beyond the Four ’P’s of marketing. The marketers and the marketing practices keep on evolving with the changing times. Today, the organisations like GODREJ, CEAT and many others which have served Indian markets for the years are busy with brand makeovers. Every marketer is trying to connect with its customers in all possible manners. The advertising and promotion done by the marketers has progressed from print and broadcast media to more customized and interactive digital/online media to ambient media. The marketers have ensured the product availability right from the physical retail stores (brick) to online/e-stores (click). This paper attempts to bridge the gap between the present day customers and marketers. It highlights the emerging socio-cultural trends in the consumer markets. The paper proposes the new marketing mix strategies and practices required by the marketers to target young and modern India.